2004
DOI: 10.1136/emj.2004.014324
|View full text |Cite
|
Sign up to set email alerts
|

Less IS less: a randomised controlled trial comparing cautious and rapid nalbuphine dosing regimens

Abstract: Objective: This study aimed to determine which of two paramedic administered nalbuphine dosing regimens combined the greater analgesic effect with the minimum of adverse events. Methods: Patients suffering from chest pain or trauma were randomised to receive either a rapid dosing regimen (10 mg over 30 seconds, repeated once after three minutes if pain score remained above three) or a cautious regimen (5 mg over two minutes, repeated at three minute intervals if pain score remained above three to a maximum dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Four pre-hospital controlled-trials investigating general trauma were conducted in the UK NHS. 100,[133][134][135] No pre-hospital trials concerning head-injury, conducted in the UK, could be identified. The remaining 11 studies were conducted in the USA, [136][137][138][139] (Table 25) summarising the appraisal of the four trials conducted in the UK NHS, upon which the discussion will focus, is presented below (the complete appraisal tables can be found in Appendix E (see Critical Appraisal tables).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four pre-hospital controlled-trials investigating general trauma were conducted in the UK NHS. 100,[133][134][135] No pre-hospital trials concerning head-injury, conducted in the UK, could be identified. The remaining 11 studies were conducted in the USA, [136][137][138][139] (Table 25) summarising the appraisal of the four trials conducted in the UK NHS, upon which the discussion will focus, is presented below (the complete appraisal tables can be found in Appendix E (see Critical Appraisal tables).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is only relevant to those studies which aimed to recruit patients whose injuries could not be fully diagnosed in the pre-hospital environment. Woollard et al 134 Snooks et al 135 Mason et al…”
Section: Relevance Of Participants Recruitedmentioning
confidence: 99%
“…A comparison of 5 mg and 10 mg nalbuphine doses given IV and repeated at 3-minute intervals to a total of 20 mg, showed that use of the larger dose led to better pain relief but higher patient-reported drowsiness; over half the patients in both groups still had significant pain on arrival at the hospital (Woollard et al, 2004 Level II).…”
Section: Chaptermentioning
confidence: 99%
“…As in other settings, pain intensity is best assessed using patient self-report measures such as VASs (Galinski et al, 2005;Kober et al, 2002), VNRSs (McLean et al, 2004;Woollard et al, 2004;Rickard et al, 2007;Bounes et al, 2008), VDSs (McLean et al, 2004;Vergnion et al, 2001), faces pain scales (Rogovik & Goldman, 2007) (see Section 2). A ruler incorporating both visual analogue and faces pain scales (Lord & Parsell, 2003 Level IV) has also been used to measure pain in patients prior to arrival at hospital.…”
Section: Assessment Of Pain In the Prehospital Environmentmentioning
confidence: 99%
“…The excluded analgesics were NSAIDs [ketorolac (Wright et al, 1994;Turturro et al, 1995;Neighbor and Puntillo, 1998;Rainer et al, 2000), mefenamic acid (Stableforth, 1977;Sleet and Khan, 1980), diflunisal (Aghababian, 1986) and piroxicam (Morán, 1990)], opioids [nalbuphine (Stene et al, 1988;Chambers and Guly, 1994;Hyland-McGuire and Guly, 1998;Woollard et al, 2002Woollard et al, , 2004, hydrocodone (Marco et al, 2005) and butorphanol (Scott et al, 1994)] and a type of paracetamol [hydrocodoneacetaminophen (Turturro et al, 1998)]. This may have led to the loss of relevant information for emergency care settings in other countries.…”
Section: Limitations In Literature Search and Analysismentioning
confidence: 99%